2013
DOI: 10.1038/pr.2013.66
|View full text |Cite
|
Sign up to set email alerts
|

Placebo effects in children: a review

Abstract: Of more than 155,000 PubMed citations found with the search term "placebo, " only ~9,000 (5.8%) included the terms "children" or "adolescents. " When all these papers were screened, only ~2,000 of them investigated the placebo effect per se, and of those, only ~50 (2.5%) discussed the placebo effect in children and adolescents. In this narrative review, we explore four aspects of the placebo response in children and adolescents: (i) the legal and ethical limitations and restrictions for the inclusion of childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
125
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(140 citation statements)
references
References 76 publications
9
125
2
2
Order By: Relevance
“…It has been suggested that children and adolescents generally show larger PR than adults (6,8). Our experimental approach clearly confirms this age effect.…”
Section: Placebo Analgesia Responsessupporting
confidence: 86%
See 2 more Smart Citations
“…It has been suggested that children and adolescents generally show larger PR than adults (6,8). Our experimental approach clearly confirms this age effect.…”
Section: Placebo Analgesia Responsessupporting
confidence: 86%
“…The literature regarding gender difference of PR is sparse and equivocal (62), and analyses of gender-specific PR in the pediatric population have been especially neglected (8). Whereas some reviews failed to find differences (63) others have reported a slight placebo susceptibility advantage for girls in a migraine headache review (64).…”
Section: Gender-dependent Differences In Pamentioning
confidence: 99%
See 1 more Smart Citation
“…While studies have reported a significant placebo response in adult patients (such as those with Parkinson's Disease [293]), placebo response rates are particularly high among children and adolescents in a subset of disorders, including psychiatric (anxiety, major depression, and obsessive compulsive and attention deficit disorders), medical (asthma), and painful (migraine, gastrointestinal) conditions [294,295]. As the current RCTs of CBD primarily target children with severe epilepsy, this may be an important issue.…”
Section: Placebo Effectmentioning
confidence: 99%
“…The reason for this is unknown, requiring further investigation, but study design is known to influence clinical trial success as well. Higher placebo responses have been observed in studies where the chances of receiving active treatment exceed 50% because there is a high expectation of improvement, [30,31] thus leading to poor discrimination between treatment groups. This study randomized subjects 2:1 active to placebo (67% chance of receiving active treatment) in part because of the observation that prospective participants in other food therapy trials with 1:1 randomization schemes were declining participation due to a high likelihood of receiving placebo treatment.…”
Section: Discussionmentioning
confidence: 99%